Fosl1 is vital to heart regeneration upon apex resection in adult Xenopus tropicalis - Hai-Yan Wu (Nature Portfolio, 2021)
Abstract Cardiovascular disease is the leading cause of death in the world due to losing regenerative capacity in the adult heart. Frogs possess remarkable capacities to regenerate multiple organs, including spinal cord, tail, and limb, but the response to heart injury and the underlying molecular mechanism remains largely unclear. Here we demonstrated that cardiomyocyte proliferation greatly contributes to heart regeneration in adult X. tropicalis upon apex resection. Using RNA-seq and qPCR, we found that the expression of Fos-like antigen 1 (Fosl1) was dramatically upregulated in early stage of heart injury. To study Fosl1 function in heart regeneration, its expression was modulated in vitro and in vivo. Overexpression of X. tropicalis Fosl1 significantly promoted the proliferation of cardiomyocyte cell line H9c2. Consistently, endogenous Fosl1 knockdown suppressed the proliferation of H9c2 cells and primary cardiomyocytes isolated from neonatal mice. Taking use of a cardiomyocyte-specific dominant-negative approach, we show that blocking Fosl1 function leads to defects in cardiomyocyte proliferation during X. tropicalis heart regeneration. We further show that knockdown of Fosl1 can suppress the capacity of heart regeneration in neonatal mice, but overexpression of Fosl1 can improve the cardiac function in adult mouse upon myocardium infarction. Co-immunoprecipitation, luciferase reporter, and ChIP analysis reveal that Fosl1 interacts with JunB and promotes the expression of Cyclin-T1 (Ccnt1) during heart regeneration. In conclusion, we demonstrated that Fosl1 plays an essential role in cardiomyocyte proliferation and heart regeneration in vertebrates, at least in part, through interaction with JunB, thereby promoting expression of cell cycle regulators including Ccnt1.